Table Partitioning Technology Based on Massive Data - Peng Wang; Ai-xue Tian; Chang Guo (Institute of Advanced Engineering and Science, 2014)
In the Logistics Distribution System, in order to enhance the availability of massive data table, simplify the maintenance operations of data table, balance disk I/O and improve query performance, this system uses the range partitioning technology, interval partitioning technology, reference partitioning technology and list partitioning technology supported by Oracle 11g. Compared to retrieve the non-partitioned table and the partition table has been used time, execution plan and statistical information. Through analysis and comparison examples show that mass data table using partitioning technologies, can improve the SQL retrieval performance, and reduce execution costs. Therefore, the contribution of table partitioning technology on massive data tables is to improve the manageability and availability of data tables, and optimizing SQL retrieval performance. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4455